(3LGeY CSQGQ GdWHs - (3RgQ Hf YHO Gdedc Hf eMeO Hf RgQ GdGTHjdj, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3bGd GdhRjQ GdMcje CHh GdYdGA Hf RgQ QMeg Gddg (B: (3GYde faYfG Gddg hEjGc Cf LSe GdEfSGf BNQ GdJQcjH s
(3BNQgG (B:s
(3OhGA ddMeh eLQH (B: (3jDNO WHGTjQ hUfOd jUfY ef GdLejY ZHGQ hjTQH HeGA aGJQ aEfg fGaY Ef TGA Gddg JYGdi ced GdcJGH s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(532 / 1 (3O(B) s
Keywords: (3GdWHs